PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN KEMAMPUAN MEMAINKAN ALAT MUSIK PIANIKA DI SEKOLAH DASAR - Annisa Fitri Bestari (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by the low ability of children to play pianica instrument in grade V students of 012 Lubuk Terentang. This research is a classroom action research conducted aimed at improving children’s ability in playing pianica musical instruments by applying a direct learning model. The subject of this research is grade V students SDN 012 Lubuk Terentang with 8 sstudents. Data collection instruments in this thesis are teacher activity sheets and student activities as well as student ability assessment sheets in playing pianica music instrument. This thesis presents preliminary data before apllying the learning model directly obtaining a base score of 40,62, increased to 53,36 in cycle I. In cycle II the ability increases to 64,82. In cycle III it increases to 81,17. Teacher activity in the first cycle of the first meeting obtained a percentage of 35% categoris less. At the second meeting increased by a percentage of 40% categoris less, at the third meeting with a percentage of 50% less categories. The first two meetings cycle obtains a percentage of 70% enough categories, at the second meeting the percentage obtained 75% good category, at the third meeting the percentage obtained 80% good category. Then the third cycle of the first meeting teacher activity also increased with a percentage of 85% good category, at the second meeting the percentage obtained 90% excellent category, and the third meeting obtained a percentage of 95% in the excellent category. In the results of this study students begin to understand the material of pianica musical instruments after applying the learning model directly marked by an increase in teacher activity and student activity in each cycle.The results of research in class V SDN 012 Lubuk Terentang prove that the application of direct learning models can improve the ability of children to play pianica instruments in grade V students of SDN 012 Lubuk Terentang Kecamatan Gunung Toar Kabupaten Kuantan Singingi.